Art Coaching as an Integrative Method for Activating Creative Thinking: Theory, Methodology, and Practical Application - Vengrzhnovskaia T. M. (Coaching and mentoring: theory and practice, 2025)
This article presents an author's method of art coaching, developed and tested since 2015. It explores the theoretical foundations and practical application of the method, which combines the structured approach of classical coaching with creative techniques of art therapy. The structure of an art coaching session, the specifics of applying the method in various areas (individual counseling, family relationships, business environment), as well as its effectiveness in solving strategic and creative tasks are examined. Special attention is paid to the scientific justification for using creative thinking to activate subconscious resources and find non-standard solutions.
Keywords: арт-терапия; креативность; creativity; стратегическое развитие; strategic development; творческое мышление; креативное мышление; ТРИЗ; creative thinking; art therapy; коучинг; подсознание; TRIZ; coaching; арт-коучинг; проективные техники; бизнес-консультирование; диагностика бизнеса; art coaching; creative mindset; subconscious; projective techniques; business consulting; business diagnostics